A New Genus and Species of pompiline Spider Wasp from Northern South America (Hymenoptera, Pompilidae: Pompilinae: Priochilini) - Wasbauer, Marius S.; Kimsey, Lynn S. (Zootaxa, 2019)
Pompiliodon gen. nov. and its type species Pompiliodon katina sp. nov. are described and illustrated. The relationships to related genera (Priochilus Banks, 1944 and Balboana Banks, 1925) are discussed.